INOVASI DAN KREATIVITAS PUBLIC SERVICE DALAM ERA OTONOMI DAERAH SEBAGAI MODERN LOCAL GOVERNMENT - Afifuddin Afifuddin (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2021)
The implementation of public services is still going on with the old public administration practices. Therefore, it is time for the bureaucracy to change its mindset. The development of the paradigm of public administration can bring enlightenment to the bureaucracy. Public Service innovation and creativity is one of the right solutions in the era of regional autonomy in achieving the welfare of modern regional government. So that innovation and creativity are needed to translate public interest in accelerating the goal of regional autonomy, namely nation building. This study raised the formulation of the problem; (1). How is the innovation and creativity of public service in the era of regional autonomy as a modern local government? (2). What are the supporting and inhibiting factors for implementing innovation and creativity in public service in the era of regional autonomy as modern local government in Indonesia? This study was designed using qualitative methods with interactive techniques. The results of this study are expected to find new concepts that can be applied in improving public servicesÂ in Indonesia, and to realize these innovations the government needs space for creativity.